Applied Aspects of Ultrasonography in Humans - Ainslie, Phil (IntechOpen, 2012)
Written by international experts, this publication provides the reader with the present knowledge and future research directions of diagnostic and therapeutic ultrasound and spectroscopy. Focused topics include Duplex ultrasound, transcranial color Duplex, MRA guided Doppler ultrasonography and near-infrared spectroscopy. New directions in the use and application of transcranial and color Duplex ultrasound are provided, as well as the use of ultrasound and arterial stiffness for measuring human vascular health and circulatory control. Novel use of ultrasound for the detection of intra-cardiac and intra-pulmonary shunts is also described along with its utility for the assessment of gastric regulation and emptying.